A Multi-Institutional Randomized Controlled Trial to Investigate Whether Zoledronate Prevents Bone Loss After Discontinuation of Denosumab: The Study Protocol of Denosumab Sequential Therapy (DST) Trial - Lee, Chia-Che; Wang, Chen-Yu; Hung, Chih-Chien; Huang, Chuan-Ching; Li, Chung-Yi; Chen, Hsuan-Yu; Chang, Yun-Liang; Tseng, Wo-Jan; Wang, Ting-Ming; Yang, Rong-Sen; Wong, Tze-Hong; Fu, Shau-Huai (Frontiers in Medicine, 2021)
Background: Though denosumab is an effective treatment for osteoporosis, the rebound effect after discontinuation has drawn investigators' attention. It includes a dramatic loss of gained bone mineral density (BMD) and an increased risk of vertebral fractures. This prospective multi-institutional randomized controlled trial aims to investigate whether zoledronate prevents loss of BMD after discontinuation of denosumab. The trial was registered as Denosumab Sequential Therapy (DST) trial in March 2019 at clinicaltrials.gov, with the identifier NCT03868033. Methods: The study is conducted at National Taiwan University Hospital and its branches. Patients who have continuously received denosumab treatment for two or more years are surveyed for eligibility. Baseline characteristics and questionnaires of life quality are recorded after recruitment. BMD, circulating levels of bone turnover markers (BTMs), including serum N-terminal propeptide of type 1 collagen (P1NP) and C-terminal telopeptide (CTX), are checked before the stratified randomization to 4 groups. Biological sex and the T-scores are used to create 4 strata. The participants in group 1 adhere to regular denosumab therapy for another 2 years. All the other patients receive on-time zoledronate treatment in the first year. The participants in group 2, 3, and 4 have on-time denosumab, on-time zoledronate and drug holiday in the second year, respectively. BMDs are checked annually. Pre-scheduled checkpoints of BTMs are also arranged. For patient safety, rescue treatment with another injection of zoledronate will be applied to the patients on drug holiday if the CTX levels raise above the pre-specified threshold, 0.573 ng/mL for women and 0.584 ng/mL for men. The primary outcomes are the percentage changes of BMDs in lumbar spine, total hip and femoral neck. The secondary outcomes include the changes of serum level of the BTMs, new osteoporotic fractures, extra zoledronate injections needed in group 4 and the differences of quality of life. Discussion: We aim to provide evidence whether zoledronate prevents bone loss after denosumab cessation. To our knowledge, the study has the largest sample size. No other randomized controlled study included all the three different treatment strategies and a positive control. It is also the first associated randomized controlled trial outside Europe.